Neglecting the Merit System in The Recruitment of Employees in Village-Owned Enterprises - Yogahastama, Riesta; Khilmatus Shokhikhah, Zilda; Putri, Marshanda Hana Amelia (Faculty of Law, Mulawarman University, 2025)
Village-owned enterprises have an important role in local economic development and the welfare of rural communities. This research aims to analyze the implementation of meritocracy principles in the BUMDes workforce recruitment process in Sampang Regency. The method used is descriptive qualitative, with primary data collection through in-depth interviews and secondary data from related documents. The results showed that the neglect of the meritocracy system in the recruitment of village-owned enterprises, such as the practice of nepotism and lack of transparency, resulted in a decrease in the quality of human resources and organizational efficiency. In addition, unfairness in recruitment has the potential to cause urbanization of qualified young people, hindering their contribution to village development. The implementation of a fair and transparent meritocracy system is expected to improve the accountability and productivity of BUMDes, and support the sustainable development of local potential.